THE IMPACT OF MINDFULNESS TRAINING ON IMPROVING COGNITIVE FLEXIBILITY AND REDUCING ACADEMIC STRESS AMONG SECONDARY SCHOOL STUDENTS. - Thomas, Jins; China, Barnali (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The purpose of the existence of schools seems to be misunderstood by a large population of educators today. Schools which are expected to be happy learning places have turned in to pyres of creativity and critical thinking. This research article examines whether mindfulness training improves cognitive flexibility and reduces academic stress in high school students using a qualitative survey method. Cognitive flexibility is an executive function of the human brain but can get severely impaired in stressful environments. Students’ learning out come depends largely on their ability to control emotions. This paper uses in-depth survey responses from students who participated in an eight-week mindfulness training program to discuss perceived benefits and challenges associated with incorporating mindfulness practices into educational settings.